Singlet oxygen generation in light-assisted peroxymonosulfate activation by carbon nitride: Role of elevated crystallinity. (April 2023) - Chen, Beizhao; Liu, Xun; Liu, Bei; Han, Qi; Li, Li; Wang, Li; Shu, Yufei; Zang, Linlin; Zhu, Wenlei; Wang, Zhongying
Abstract: Carbon nitride (CN) is an emerging 2D non-metal semiconductor material that could be used in photocatalysis and advanced oxidation processes (AOPs) for pollutants degradation. The radical-induced degradation by CN in photocatalysis or photo-assisted AOPs was widely reported in previous studies. Nevertheless, how the non-radical degradation by CN materials could be achieved under irradiation is neither well understood nor controlled. In this work, crystalline carbon nitride (CCN) was synthesized via a facile molten-salt method, and used to activate peroxymonosulfate (PMS) under visible light (>420 nm) to selectively and efficiently degrade tetracycline (TC). Compared to the traditional polymeric carbon nitride (PCN), CCN was found to be a superior PMS activator with the assistance of visible light, which was ascribed to the increased crystallinity of CN tri-s-triazine units and the increased number of catalytic sites, thereby optimizing the photoelectric properties. The activation performance could be further improved by copper loading, with TC degradation rate nearly six times more than that of PCN. EPR trapping and quenching tests showed that singlet oxygen ( 1 O2 ) was the dominant reactive oxygen species in the CCN/PMS/visible light system, attributing to the increased graphitic N sites and formation of electron-deficient C in C–N bonding between neighboring tri-s-triazine units upon crystallinity elevation in CCN. In contrast to the conventional radical-based photocatalysis and AOP processes, the visible light-assisted non-radical AOP degradation was highlighted for the selectivity and the remarkable resistance to the impacts of background inorganic anions or natural organic matter (up to 10 mg/L) in the actual water matrix. This work revealed the 1 O2 generation mechanism by CN-based materials under the joint assistance of visible light illumination and crystallinity elevation, and its excellent removal performance demonstrates the great potential of CCN-based materials in the practical wastewater treatment. Graphical abstract: Image 1 Highlights: Crystalline carbon nitride (CCN) materials was synthesized on the basis of polymeric carbon nitride (PCN). CCN exhibited superior catalytic degradation for tetracycline over conventional PCN. Photoelectric properties were optimized upon elevated crystallinity in CCN. CCN was found favorable for 1 O2 generation due to the increased graphitic N sites. The non-radical oxidation mechanism was first reported and highlighted in CCN/PMS/light system.